Prevalence and determinants of tobacco use and oral sub mucous fibrosis in auto-rickshaw drivers at Bareilly, Uttar Pradesh, India - Singhal, Aditya; Agrawal, Pooja; Agrawal, Vijender Kumar (International Surgery Journal, 2018)
Background: Around 34.6% of Indian population consumes tobacco. The tobacco consumption is higher in some vulnerable population such as drivers, daily wage laborers, and policemen. Tobacco consumption is known to cause oral cancers, and screening for oral cancer in these individuals is known to reduce mortality from cancer. The study was designed to assess the determinants of tobacco use and the prevalence of oral precancerous lesions in auto-rickshaw drivers. Methods: This is a cross-sectional study among auto-rickshaw drivers at Bareilly (UP). A total of 450 auto-rickshaw drivers were enrolled in the study, of which 225 auto-rickshaw drivers were interviewed during morning hours and remaining half at night time using a semi-structured questionnaire. All were screened for oral cancer/precancerous lesions. Results: Nearly 64.44% of auto-rickshaw drivers were consuming tobacco in any form. Long working hours, working at night, and family members consuming tobacco were significant risk factors for tobacco use among auto-rickshaw drivers. 56 (19.31%) auto-rickshaw drivers were detected to have oral precancerous lesions. Conclusions: It was very evident that long hours of driving and infrequent shifts played a greater role in acquiring the habit. Behavioral counselling and new laws need to be formed to limit the working hours in drivers to have an effective tobacco control.